Statistical evaluation of ozone concentrations on open plots in a submountain beech ecosystem in the Western Carpathians Mts - Kellerova, D., Slovak Academy of Sciences, Zvolen (Slovak Republic). Inst. of Forest Ecology; Janik, R., Slovak Academy of Sciences, Zvolen (Slovak Republic). Inst. of Forest Ecology (Časopis Beskydy, 2013)
The research was conducted on two plots withouth forest cover situated in the Stiavnicke vrchy (A) Mts and in the Kremnicke vrchy (B) Mts (Western Carpathian region, Slovak Republic) and a plot covered with several-year-old naturally regenerated beech stand (C) in the Kremnicke vrchy Mts. The highest average value of 71 micrograms/cubic m was recorded in 2007 for all plots; the lowest one was 45 micro g/cubic m recorded in 2009. Maximum values of ground level zone concentrations ranging from 124 to 144 micro g/cubic m were recorded in spring 2008 on all study plots. The values were displaying fairly high variability over the whole research period, with minima in years 2007 and 2008 on the plot covered with forest stand at the time. Statistically significant differences were distinct especially between the years 2007 and 2009.